The Crosstalk Between Regulatory Non-Coding RNAs and Nuclear Factor Kappa B in Hepatocellular Carcinoma - Zhang, Yina; Shao, Jiajia; Li, Shuangshuang; Liu, Yanning; Zheng, Min (Frontiers in Oncology, 2021)
Hepatocellular carcinoma (HCC) is a highly lethal type of malignancies that possesses great loss of life safety to human beings worldwide. However, few effective means of curing HCC exist and its specific molecular basis is still far from being fully elucidated. Activation of nuclear factor kappa B (NF-κB), which is often observed in HCC, is considered to play a significant part in hepatocarcinogenesis and development. The emergence of regulatory non-coding RNAs (ncRNAs), particularly microRNAs (miRNAs) and long non-coding RNAs (lncRNAs), is a defining advance in cancer biology, and related research in this branch has yielded many diagnostic and therapeutic opportunities. Recent studies have suggested that regulatory ncRNAs act as inhibitors or activators in the initiation and progression of HCC by targeting components of NF-κB signaling or regulating NF-κB activity. In this review, we attach importance to the role and function of regulatory ncRNAs in NF-κB signaling of HCC and NF-κB-associated chemoresistance in HCC, then propose future research directions and challenges of regulatory ncRNAs mediated-regulation of NF-κB pathway in HCC.